2021
DOI: 10.1002/adsc.202100819
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mutualism in Organic Synthetic Chemistry: Mutually Promoted C−H Functionalization of Indole and Reduction of Quinoline

Abstract: Here we reported a one‐pot, metal‐free B(C6F5)3‐catalyzed strategy for simultaneous synthesis of C3‐regioselective functionalization of indoles and complete reduction of quinolines. It turned out that by sharing a quinolinium hydridoborate intermediate, the original determining steps with high energy barrier in both the convergent disproportionation of indole and reduction of quinoline could be realized at room temperature, thus furnishing both the C3‐borylated (or silylated) indoles and N‐borylated tetrahydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…7b and 7c and DFT results 11,44 . The concerted activation of the Si-H bond in Ph 2 SiH 2 by B(C 6 F 5 ) 3 and 1a is similar to that in hydrosilylation/hydroboration reactions catalyzed by B(C 6 F 5 ) 3 reported previously [45][46][47][48][49][50] .…”
Section: Research On the Reaction Mechanismsupporting
confidence: 78%
“…7b and 7c and DFT results 11,44 . The concerted activation of the Si-H bond in Ph 2 SiH 2 by B(C 6 F 5 ) 3 and 1a is similar to that in hydrosilylation/hydroboration reactions catalyzed by B(C 6 F 5 ) 3 reported previously [45][46][47][48][49][50] .…”
Section: Research On the Reaction Mechanismsupporting
confidence: 78%
“…utilized B(C 6 F 5 ) 3 to rapidly polymerize α‐diketone and bis(silane) monomers into high molecular weight poly(silyl‐ether)s under ambient conditions. [ 54 ] After analyzing the previous literatures and our research work related to the boron chemistry, [ 55‐59 ] we focused our research interests on the design and development of new element reactions for polymer synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous review, 6 we observed how hydride abstraction had been utilized in the dehydrogenation of a variety of benzofused N -heterocycles, 29 as well as the dehydrogenative coupling of indoles with silanes and boranes. These reactions are believed to proceed via an acceptorless dehydrogenation pathway, where an ammonium borohydride intermediate (generated after hydride abstraction and iminium tautomerization) undergoes an acid–base reaction to evolve H 2 .…”
Section: Dehydrogenation Of Aminesmentioning
confidence: 99%